Double heterozygosity for mutations in the β-myosin heavy chain and in the cardiac myosin binding protein C genes in a family with hypertrophic cardiomyopathy. Issue 7 (1st July 1999) - Richard, Pascale; Isnard, Richard; Carrier, Lucie; Dubourg, Olivier; Donatien, Yves; Mathieu, Bénédicte; Bonne, Gisèle; Gary, Françoise; Charron, Philippe; Hagege, Albert; Komajda, Michel; Schwartz, Ketty; et al.
Abstract : Familial hypertrophic cardiomyopathy is a genetically heterogeneous autosomal dominant disease, caused by mutations in several sarcomeric protein genes. So far, seven genes have been shown to be associated with the disease with the β-myosin heavy chain (MYH7) and the cardiac myosin binding protein C (MYBPC3) genes being the most frequently involved. We performed electrocardiography (ECG) and echocardiography in 15 subjects with hypertrophic cardiomyopathy from a French Caribbean family. Genetic analyses were performed on genomic DNA by haplotype analysis with microsatellite markers at each locus involved and mutation screening by single strand conformation polymorphism analysis. Based on ECG and echocardiography, eight subjects were affected and presented a classical phenotype of hypertrophic cardiomyopathy. Two new mutations cosegregating with the disease were found, one located in the MYH7 gene exon 15 (Glu483Lys) and the other in the MYBPC3 gene exon 30 (Glu1096 termination codon). Four affected subjects carried the MYH7 gene mutation, two the MYBPC3 gene mutation, and two were doubly heterozygous for the two mutations. The doubly heterozygous patients exhibited marked left ventricular hypertrophy, which was significantly greater than in the other affected subjects. We report for the first time the simultaneous presence of two pathological mutations in two different genes in the context of familial hypertrophic cardiomyopathy. This double heterozygosity is not lethal but is associated with a more severe phenotype.